2001
DOI: 10.1097/00005768-200108000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between subcutaneous fatness and leptin in male athletes

Abstract: The results suggest that estimates of adiposity and metabolic parameters are associated with leptin in a sport-specific manner. Whereas leptin might be regulated by overall subcutaneous fatness in athletes, our study does not imply a main influence of fat patterning on leptin in this group of trained subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
2
11
0
1
Order By: Relevance
“…Although significant changes in fat percentage were detected in this study, the subjects actually had quite a low absolute body fat mass (i.e., less than 2.0 kg) and low plasma leptin concentrations. Previous reports also suggested that the typical characteristics of male endurance runners are low body fat mass and a low blood leptin level (Hickey et al, 1996;Sudi et al, 2001). In contrast, it is known that body fat mass is closely related to plasma leptin concentration in non-athletes Koistinen et al, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…Although significant changes in fat percentage were detected in this study, the subjects actually had quite a low absolute body fat mass (i.e., less than 2.0 kg) and low plasma leptin concentrations. Previous reports also suggested that the typical characteristics of male endurance runners are low body fat mass and a low blood leptin level (Hickey et al, 1996;Sudi et al, 2001). In contrast, it is known that body fat mass is closely related to plasma leptin concentration in non-athletes Koistinen et al, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…Uma falha na sua produção e/ou na sua ação sobre os receptores hipotalâmicos poderia desequilibrar positivamente o balanço energético, gerando o quadro de obesidade (12). No entanto, estudos realizados em humanos mostram que os níveis plasmáticos de leptina são elevados em obesos quando comparados com seus congêneres magros (16,(33)(34)(35). Crianças pré-púberes e adolescentes obesos também apresentam níveis de leptina mais elevados do que indivíduos magros da mesma faixa etária (36).…”
Section: Mecanismos De Ação Da Leptina Na Ingestão Alimentarunclassified
“…In humans, the systemic leptin level has been reported to be proportional to the body fat mass [2, 3]. In trained subjects, the circulating leptin level is low, and even at biologically extremely low levels of body fat, the leptin concentration is closely related to the body fat content in male athletes [3, 4]. …”
Section: Introductionmentioning
confidence: 99%
“…An exercise-mediated negative energy balance may contribute to the regulation of plasma leptin levels and presumably leptin action [3, 4]. Furthermore, it has recently been suggested that the regulation of leptin may also depend on factors at the metabolic level associated with certain long-term exercise regimens [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation